Pengaruh Sistem Kerja Dan Kesejahteraan Terhadap Kinerja Tenaga Outsourcing Di PT.PLN (Persero) Rayon Ampera Palembang - Ariyani, Arika; ., Heriyanto; ., Trisninawati; Roni, Mukran (CV. ITTC INDONESIA, 2024)
This study aims to evaluate the impact of work systems and welfare on the performance of outsourcing employees at PT.PLN (Persero) Rayon Ampera Palembang. The research employed a population method, with all 40 outsourcing employees serving as the sample, using total sampling techniques. Data was collected through questionnaires utilizing a Likert scale as the measurement tool. The study used a quantitative approach, incorporating validity and reliability tests, classical assumption tests, multiple linear regression analysis, as well as t-tests, F-tests, and determination tests, all conducted using SPSS version 25 software. The findings indicate that both the work system and welfare variables positively influence the performance of outsourcing employees, both individually and collectively.